Current status and recommendations for biomarkers and biobanking in neurofibromatosis. (16th August 2016) - Hanemann, C. Oliver; Blakeley, Jaishri O.; Nunes, Fabio P.; Robertson, Kent; Stemmer-Rachamimov, Anat; Mautner, Victor; Kurtz, Andreas; Ferguson, Michael; Widemann, Brigitte C.; Evans, D. Gareth; Ferner, Rosalie; Carroll, Steven L.; et al.
Abstract : Objective: Clinically validated biomarkers for neurofibromatosis 1 (NF1), neurofibromatosis 2 (NF2), and schwannomatosis (SWN) have not been identified to date. The biomarker working group's goals are to (1) define biomarker needs in NF1, NF2, and SWN; (2) summarize existing data on biomarkers in NF1, NF2, and SWN; (3) outline recommendations for sample collection and biomarker development; and (4) standardize sample collection and methodology protocols where possible to promote comparison between studies by publishing standard operating procedures (SOPs). Methods: The biomarker group reviewed published data on biomarkers in NF1, NF2, and SWN and on biobanking efforts outside these diseases via literature search, defined the need for biomarkers in NF, and developed recommendations in a series of consensus meetings. Results: We describe existing biomarkers in NF and report consensus recommendations for SOP and a minimal clinical dataset to accompany samples derived from patients with NF1, NF2, and SWN in decentralized biobanks. Conclusions: These recommendations are intended to provide clinicians and researchers with a common set of guidelines to collect and store biospecimens and for establishment of biobanks for NF1, NF2, and SWN.